The effect of silver nanoparticles toward properties and antibacterial activity of silver-alginate nanocomposite films - Susilowati, Endang; Mahardiani, Lina; Hardini, Retno Duwi (Frontiers in Sustainable Food Systems, 2022)
Preparation of silver-alginate nanocomposite films as an antibacterial material has been carried out through the casting method of colloidal nanocomposite silver-alginate. Colloidal was made by chemical reduction of AgNO3 precursor salts using microwave irradiation with alginate as a stabilizer and reducing agent and NaOH as an accelerator. The appearance of a brownish yellow color, due to the addition of variation of AgNO3, and the localized surface plasmon resonance (LSPR) phenomenon were identified by UV-Vis spectrophotometer, indicating that silver nanoparticles have been formed. The properties of obtained silver nanoparticles was then examined. The shape and size distribution of silver particles were determined based on the image on transmission electron microscopy (TEM), chemical properties (FTIR), mechanical, crystallinity (XRD), and surface morphology (SEM). Testing of antibacterial activity was performed on silver-alginate nanocomposite films using the diffusion method for gram-positive (S. aureus and MRSA) and gram-negative (E. coli and ESBL) bacteria. The results showed that based on the UV-Vis spectrophotometer characterization results, the LSPR phenomenon appeared at the absorption peak of 401.01–409.00 nm, denoting silver nanoparticles with a spherical shape of 3–22 nm have been formed. Further, the presence of silver nanoparticles affected the mechanical properties of the film, where the tensile strength of the film tended to decrease with the increase in the silver nanoparticles concentration while the crystallinity increased. Next, based on the SEM results the nanocomposite films of silver-alginate had a rough and porous structure. The nanocomposite film had antibacterial activity against E. coli, S. aureus, ESBL, and MRSA. The antibacterial activity film was affected by the concentration of silver nanoparticles.